Zirconite composite material resistant to high-alkali glass erosion and preparation method thereof
By adding components such as yttrium phosphate powder and modifier to zircon materials and adopting sintering process, the problem of decomposition of zircon materials under high alkali glass is solved, and its corrosion resistance and application range at high temperatures are significantly improved.
Patent Information
- Application Number
- CN202510336107.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-21
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-21
AI Technical Summary
The existing zircon materials will decompose when they come into contact with overalkali glass above 1050°C, resulting in glass defects, limiting their application range in glass kilns.
A composite material including zircon powder, yttrium phosphate powder, modifier and sintering promoter is used to form green body by wet grinding and isostatic molding, and then sintered to obtain a zircon composite material that is resistant to high alkali glass erosion.
When contacting the overalkali glass at 1050℃, 1150℃ or even 1300℃, the material has no zircon decomposition phenomenon, and the decomposition temperature has been increased by 100-250℃, which has expanded the application range of zircon materials, and the volume density and porosity of the material have reached 4.35g/cm3 and ≤0.6%, which has significantly improved its performance at high temperatures.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of zircon products, and in particular to a zircon composite material resistant to high-alkali glass corrosion and a preparation method thereof. Background Art
[0002] Zircon has the advantages of low thermal expansion, high temperature resistance, good thermal shock resistance, and excellent resistance to slag and alkali-free glass corrosion. It is widely used in the crown of the glass furnace, fire holes, detection holes, breast walls of the melting part, and the bottom sealing layer of the tank. Extensive research has been conducted on zircon materials for glass furnaces: Chinese invention patent CN102584286A discloses a creep-resistant zircon refractory material used in glass manufacturing systems. The material comprises the following components: ZrSiO4: 98.85-99.68 wt.%, ZrO2: 0.01-0.15 wt.%, TiO2: 0.23-0.5 wt.%, and Fe2O3: 0.08-0.6 wt.%. This patent primarily improves the creep resistance of overflow bricks by controlling the addition of titanium oxide and iron oxide.
[0003] Chinese invention patent CN102036934B discloses a low-strain-rate modified zircon material and product. The method comprises mixing zircon particles with a multi-peak particle size distribution curve, at least 0.1% by weight of TiO2, and up to 10% by weight of Y2O3, isostatically pressing to form a green body, and sintering at at least 1500°C to obtain a dense zircon material. The method uses multi-level particle grading to improve the bulk density of the product and minimize the porosity, thereby reducing the grain boundary concentration and improving the bonding strength between the grain boundaries of the zircon particles.
[0004] Chinese invention patent CN101842325A discloses low creep zircon containing nano-additives and a preparation method thereof, wherein Class I, II, III additives and combinations thereof are added to the zircon, wherein the content of Class I additives is 0.0-0.1wt.%, selected from Fe2O3, SnO2, oxide glass and mixtures and combinations thereof; the content of Class II additives is 0.1-0.8wt.%, selected from TiO2, SiO2, VO2, CoO, NiO, NbO and mixtures and combinations thereof; the content of Class III additives is 0.1-0.8wt.%, selected from Y2O3, ZrO2, CaO, MgO, Cr2O3, Al2O3 and mixtures and combinations thereof; wherein the amount of the sintering agent is calculated as oxide, based on the percentage of the total weight of the composition, and the obtained composite material has a low creep rate and good strength at high temperature.
[0005] Chinese invention patent CN105541411A discloses zircon-based refractory products. Surface pores of zircon-based refractory products are filled with a ceramic phase, significantly reducing the surface open pore voids and pore diameters to provide zircon-based refractory materials with improved performance. An impregnation solution is formed by mixing 50 wt.% chemically pure tetraethyl orthosilicate and 50 wt.% chemically pure isopropyl alcohol. The zircon refractory products are impregnated with the solution and sintered at 1000°C for 2 hours to form a silicon oxide ceramic phase filler in the surface open pores to improve corrosion resistance.
[0006] Zircon bricks have good resistance to erosion by alkali-free glass liquids and can be used in contact with alkali-free glass liquids. However, when exposed to high-alkali glass (calculated as oxides, Na2O+K2O+Li2O in the glass, ≥5 wt.%), such as soda-lime glass and high-aluminum high-alkali cover glass, zircon decomposes into zirconium oxide and silicon oxide at temperatures above 1050°C. The flaking of zirconium oxide crystals easily forms glass defects, thus limiting the operating temperature range of zircon bricks in contact with glass. For example, Chinese invention patent CN102442760A discloses a high-static fatigue alumina isopipe. Example 1 discloses an alkali content of 10 wt.% or more, specifically 13.75 wt.%, primarily composed of Na2O and a small amount of K2O. When exposed to zircon at 1214°C, worm-like or fish-egg-like zircon oxide forms. This worm-like or fish-egg-like zircon oxide leads to zircon oxide defects in the glass, making zircon materials incompatible with high-alkali glass.
[0007] Therefore, it is necessary to improve the existing technology to find a way to inhibit the decomposition of zircon when it contacts high-alkali glass at temperatures above 1050°C, and to expand the application range of zircon materials in glass kilns. Summary of the Invention
[0008] The technical problem to be solved by the present invention is to overcome the shortcomings of the existing technology, provide a zircon composite material resistant to high-alkali glass corrosion and a preparation method thereof, solve the problem of zircon material decomposing when contacting high-alkali glass above 1050°C, and expand the application range of zircon material.
[0009] The technical solution of the present invention is: On the one hand, the present invention provides a zircon composite material resistant to high-alkali glass corrosion, comprising the following components in percentage by mass, wherein the total mass of the remaining components except the organic binder is calculated as 100%, and the organic binder is calculated as a percentage of the total mass of the remaining components: 94.2-99% zircon powder, 0.25-4.3% yttrium phosphate powder, 0.15-1% modifier, 0.2-0.6% sintering promoter, and 0.1-0.5% organic binder; wherein the modifier is aluminum dihydrogen phosphate powder or phosphoric acid solution.
[0010] Preferably, in the zircon powder, Al2O3<0.35wt.%, Fe2O3<0.15wt.%, TiO2<0.15wt.%, SiO2>32.7wt.%, and ZrO2>65.5wt.%.
[0011] Preferably, in the yttrium phosphate powder, YPO4≥99.99wt.%, and the crystal form is xenotime.
[0012] Preferably, the concentration of the phosphoric acid solution is 85 wt.%.
[0013] Preferably, the sintering promoting agent is titanium oxide powder, wherein TiO2>98.5wt.%, and the crystal form is rutile.
[0014] Preferably, the organic binder is polyvinyl alcohol.
[0015] In another aspect, the present invention provides a method for preparing the above-mentioned zircon composite material resistant to high-alkali glass corrosion, comprising the following steps: S1: Mix the components to prepare the batch; S2: wet grinding and spray granulation of the batch materials to form granulated powder, and isostatic pressing of the granulated powder to obtain a green body; S3: Sintering the green body to obtain a zircon composite material resistant to high-alkali glass corrosion.
[0016] Preferably, in step S2, the isostatic pressing pressure is 80-180 MPa.
[0017] Preferably, in step S2, the median diameter of the particles in the slurry obtained after wet grinding is 4-9 μm. The main function of wet grinding is to adjust the particle size of the zircon powder particles so that the yttrium phosphate powder, modifier, and sintering agent are evenly distributed among the zircon powder particles.
[0018] Preferably, in step S3, the sintering temperature is 1510-1580°C.
[0019] Compared with the prior art, the present invention has the following beneficial effects: 1. The zircon composite material resistant to high-alkali glass corrosion prepared by the present invention has a volume density of ≥4.35g / cm 3 , apparent porosity ≤0.6%; and compared with the decomposition phenomenon of existing zircon products at the corrosion interface of 1050℃, there is no zircon decomposition phenomenon when contacting the high-alkali glass corrosion interface at 1050℃, 1150℃ or even 1300℃, and the decomposition temperature is increased by 100-250℃, which solves the problem of decomposition of zircon materials when contacting high-alkali glass above 1050℃ and expands the application range of zircon materials.
[0020] 2. The present invention, by adding yttrium phosphate powder and a modifier, produces a dense product at relatively low temperatures, close to the sintering temperature of zircon materials (1510-1580°C), thus resolving the difficulty in sintering yttrium phosphate and zircon composites. The high-alkali glass-resistant zircon composite prepared by the present invention has a foaming index of only 1-2 at 1300°C, significantly lower than the foaming level of existing zircon products. Furthermore, the preparation method of the present invention is simple, scientific, and rational, making it suitable for large-scale industrial production. DETAILED DESCRIPTION
[0021] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0022] In the following examples, the zircon powder used contained the following components by weight: 0.3 wt.% Al₂O₃, 0.1 wt.% Fe₂O₃, 32.85 wt.% SiO₂, 0.13 wt.% TiO₂, 0.09 wt.% P₂O₅, 66.1 wt.% ZrO₂, with the remainder being trace impurities such as K₂O, Na₂O, CaO, and MgO. The zircon powder had a median diameter of 14 μm. The yttrium phosphate powder used contained ≥99.99 wt.% YPO₄, a xenotime crystal form, 61.43 wt.% Y₂O₃, and approximately 38.56 wt.% P₂O₅, essentially no other impurities. The powder had a median diameter of 5 μm. The titanium oxide powder used as a sintering promoter contained 99.1 wt.% TiO₂, a rutile crystal form, and a median diameter of 3 μm. The concentration of the phosphoric acid solution as the modifier is 85 wt.%.
[0023] The preparation method of the zircon composite material resistant to high-alkali glass corrosion in the following embodiment includes the following steps: S1: Mix the components to prepare the batch; S2: The batch material is wet-grinded and spray-granulated to form a granulated powder, and the granulated powder is isostatically pressed to produce a green body; wherein the wet grinding is to add the batch material to a ball mill at a mass ratio of zirconia balls, batch material, and water of 2:2:1 and grind to obtain a slurry; after spray-granulating the slurry, the formed granulated powder is charged into a mold, pressurized, and then reduced to normal pressure to produce a green body with a length of 400 mm, a thickness of 300 mm, and a width of 300 mm; S3: After the green body is naturally dried for 2 days, it is placed in a gas-fired kiln for sintering to obtain a zircon composite material resistant to high-alkali glass corrosion.
[0024] In the following examples, the particle sizes are all measured using a laser particle size analyzer, and the median diameter refers to the particle size corresponding to when the cumulative particle size distribution percentage of the sample reaches 50%.
[0025] Examples 1-8 The formulations and process parameters of the zircon composite materials resistant to high-alkali glass corrosion of Examples 1-8 are shown in Table 1.
[0026] Comparative Example 1 The difference from Example 3 is that no yttrium phosphate powder is added in Comparative Example 1, and its formula and process parameters are shown in Table 2.
[0027] Comparative Example 2 The difference from Example 4 is that no yttrium phosphate powder is added in Comparative Example 2, and its formula and process parameters are shown in Table 2.
[0028] Comparative Example 3 The difference from Example 7 is that no aluminum dihydrogen phosphate powder is added in Comparative Example 3, and its formula and process parameters are shown in Table 2.
[0029] Comparative Example 4 The difference from Example 8 is that no aluminum dihydrogen phosphate powder is added in Comparative Example 4, and its formula and process parameters are shown in Table 2.
[0030] Comparative Example 5 The difference from Example 1 is that the content of yttrium phosphate powder is 0.05 wt.%.
[0031] Comparative Example 6 The difference from Example 1 is that the content of yttrium phosphate powder is 5 wt.%.
[0032] Comparative Example 7 The difference from Example 1 is that the amount of phosphoric acid solution added is 0.1 wt.%.
[0033] Comparative Example 8 The difference from Example 1 is that the added amount of phosphoric acid solution is 1.4 wt.%.
[0034] Comparative Example 9 The difference from Example 1 is that yttrium silicate powder with a median diameter of 3 μm and a purity of 99.5 wt.% is used instead of yttrium phosphate powder.
[0035] Comparative Example 10 The difference from Example 1 is that yttrium-stabilized zirconium powder is used instead of yttrium phosphate powder, the Y2O3 content in the yttrium-stabilized zirconium powder used is 14.97wt.%, the ZrO2 content is 84.83wt.%, and it basically does not contain other impurity components. The median diameter of the powder is 2μm, and the yttrium content in the yttrium-stabilized zirconium powder is the same as the yttrium content in the yttrium phosphate powder in Example 1.
[0036] Table 1 Formulations and process parameters of Examples 1-8
[0037] Table 2 Formula and process parameters of Comparative Examples 1-10
[0038] The performance of the zircon composite materials of Examples 1-8 and Comparative Examples 1-10 was tested using the following method: The bulk density and porosity are tested in accordance with GB / T 2997-2015 Test method for bulk density, apparent porosity and true porosity of dense shaped refractory products.
[0039] The room temperature compressive strength is tested with reference to GB / T 5072-2023 Test method for room temperature compressive strength of refractory materials.
[0040] The high-alkali glass used in the following erosion test and foaming test has as main components Na2O and K2O totaling approximately 13 wt.%, Al2O3 approximately 23 wt.%, and SiO2 approximately 63 wt.%, and is a common commercially available high-aluminum, high-alkali cover glass.
[0041] The erosion test was conducted in accordance with JC / T 806-2017 Test Method for Static Resistance of Refractory Materials for Glass Furnaces to Liquid Glass Erosion: The specimen size was 12 mm in diameter and 70 mm in length. The test conditions were 1050°C × 100 h, 1150°C × 100 h, and 1300°C × 100 h, respectively. After erosion, the specimen was cut in half longitudinally, and the area attached to the glass was ground and polished. The specimen was observed under a polarizing microscope at ×300-400 times. If zircon decomposed into baddeleyite, the test temperature was no longer increased.
[0042] The foaming test was conducted in accordance with JC / T 639-2017 Test method for bubble precipitation rate of refractory materials for glass furnaces: the sample size was 50 mm × 50 mm × 10 mm, the test conditions were 1300 ° C × 6 h, and a glass column made by melting high-alkali glass was placed on the surface of the sample.
[0043] The test results are shown in Table 3-4.
[0044] Table 3 Performance test results of zircon composite materials resistant to high-alkali glass corrosion of Examples 1-8
[0045] Table 4 Performance test results of zircon composite materials of Comparative Examples 1-10
[0046] As shown in Table 3, the zircon composite materials resistant to high-alkali glass corrosion obtained in Examples 1-8 have an apparent porosity of 0.1-0.6% and a bulk density of 4.35-4.45 g / cm after firing.3 , compared with the foaming index of high alkali glass at 1300°C, which is mostly 1; and compared with the existing zircon material that decomposes when it comes into contact with high alkali glass at 1050°C, the erosion temperature of the high alkali resistant glass in Examples 4-5 is increased by at least 100°C, and the erosion temperature of the high alkali resistant glass in the other examples is increased by at least 250°C.
[0047] Compared with Comparative Examples 1-2, Examples 3-4 added yttrium phosphate powder, resulting in a zircon composite material with a high bulk density. No zircon decomposition occurred at the interface with high-alkali glass at 1300°C for 100 hours, and the usable temperature was increased by 250°C. In Comparative Examples 1-2, although the addition of phosphoric acid solution alone had a certain sintering-promoting effect, the bulk density of the sample did not exceed 4.3 g / cm 3 , and the foaming index is 2 times higher than that of Example 3-4. This indicates that after high-temperature sintering, the effective components of the phosphoric acid solution added alone, phosphate or phosphorus pentoxide, cannot inhibit the decomposition of zircon.
[0048] In Example 7-8, aluminum dihydrogen phosphate powder was added as a modifier, and the volume density of the prepared zircon composite material was 4.43 g / cm 3 and 4.4 g / cm 3 The porosity is only 0.2% and 0.1%, respectively. Compared with Comparative Examples 3-4 without the addition of modifier, the apparent porosity and bulk density are significantly improved. There is no zircon decomposition phenomenon at the corrosion interface with high-alkali glass at 1300℃×100h, and the foaming index is also significantly improved. In addition, in Comparative Examples 3-4, yttrium phosphate can significantly inhibit sintering, and the bulk density of the sample is only 4.26g / cm 3 and 4.08g / cm 3 , the apparent porosity reaches 6% and 9%, and the foaming index is 3. This indicates that when yttrium phosphate is added alone, the material is difficult to densify during sintering, resulting in easy penetration of high-alkali glass in the sample. In addition, yttrium phosphate itself may have a certain foaming property in high-alkali glass, which is ineffective in inhibiting the decomposition of zircon.
[0049] Comparison of Example 1 with Comparative Examples 5-8 shows that when yttrium phosphate powder and phosphoric acid solution are added simultaneously, but the amounts of yttrium phosphate powder and phosphoric acid solution added are excessive or insufficient, the bulk density of the sintered sample is low. While the foaming index at 1300°C remains high compared to high-alkali glass, zircon decomposition is absent at least at 1050°C. This further demonstrates that the reaction product of yttrium phosphate powder and phosphoric acid solution after high-temperature sintering can inhibit zircon decomposition. However, when the amounts of yttrium phosphate powder and phosphoric acid solution added are inappropriate, the decomposition-inhibiting effect is very limited.
[0050] By comparing Example 1 with Comparative Example 9, it can be seen that when yttrium silicate powder and the modifier phosphoric acid solution are added, the bulk density of the sintered sample is low, the foaming index of the high-alkali glass at 1300°C is high, and the sample has zircon decomposition at 1050°C. This shows that in the present invention, when the phosphoric acid solution is added together with the yttrium phosphate powder, the reaction product after high-temperature sintering can inhibit the decomposition of zircon, while when the phosphoric acid solution is added together with the yttrium silicate powder, this effect cannot be achieved.
[0051] Comparison of Example 1 and Comparative Example 10 shows that when yttrium-stabilized zirconium powder and phosphoric acid solution are added as a modifier, and the yttrium oxide content in the yttrium-stabilized zirconium powder is the same as that in the yttrium phosphate powder in Example 1, the sintered sample exhibits a low bulk density, a high foaming index at 1300°C, and zircon decomposition at 1050°C. It is speculated that the zirconium phosphate and yttrium phosphate products formed by the yttrium-stabilized zirconium powder and phosphoric acid solution at high temperatures are ineffective in inhibiting zircon decomposition.
Claims
1. A zircon composite material resistant to high-alkali glass corrosion, characterized in that: The invention comprises the following components in percentage by mass, wherein the total mass of the remaining components except the organic binder is calculated as 100%, and the organic binder is calculated as the percentage of the total mass of the remaining components: zircon powder 94.2-99%, yttrium phosphate powder 0.25-4.3%, modifier 0.15-1%, sintering promoter 0.2-0.6%, and organic binder 0.1-0.5%; wherein the modifier is aluminum dihydrogen phosphate powder or phosphoric acid solution.
2. The zircon composite material resistant to high-alkali glass corrosion according to claim 1, characterized in that: In the zircon powder, Al2O3<0.35wt.%, Fe2O3<0.15wt.%, TiO2<0.15wt.%, SiO2>32.7wt.%, and ZrO2>65.5wt.%.
3. The zircon composite material resistant to high-alkali glass corrosion according to claim 1, characterized in that: In the yttrium phosphate powder, YPO4≥99.99wt.%, and the crystal form is xenotime.
4. The zircon composite material resistant to high-alkali glass corrosion according to claim 1, characterized in that: The concentration of the phosphoric acid solution is 85 wt.%.
5. The zircon composite material resistant to high-alkali glass corrosion according to claim 1, characterized in that: The sintering promoting agent is titanium oxide powder, wherein TiO2>98.5wt.%, and the crystal form is rutile.
6. The zircon composite material resistant to high-alkali glass corrosion according to claim 1, characterized in that: The organic binder is polyvinyl alcohol.
7. The method for preparing the zircon composite material resistant to high-alkali glass corrosion according to any one of claims 1 to 6, characterized in that: The following steps are involved: S1: Mixing the components into a batch; S2: wet grinding and spray granulation of the batch materials to form granulated powder, and isostatic pressing the granulated powder to obtain a green body; S3: Sintering the green body to obtain a zircon composite material resistant to high-alkali glass corrosion.
8. The method for preparing the zircon composite material resistant to high-alkali glass corrosion according to claim 7, characterized in that: In step S2, the isostatic pressing pressure is 80-180 MPa.
9. The method for preparing the zircon composite material resistant to high-alkali glass corrosion according to claim 7, characterized in that: In step S2, in the slurry obtained after wet grinding, the median diameter of the particles is 4-9 μm.
10. The method for preparing the zircon composite material resistant to high-alkali glass corrosion according to claim 7, characterized in that: In step S3, the sintering temperature is 1510-1580°C.
Citation Information
Patent Citations
Low-creep-zircon material with nano-additives and method of making same
CN101842325A
Low-strain-rate modified zircon material and articles
CN102036934B
High static fatigue alumina isospipes
CN102442760A
Creep resistant zircon refractory material used in a glass manufacturing system
CN102584286A
Zirconite-base refractory product
CN105541411A
Cited By
Production process of anti-microcrack and anti-edge-breakage tempered glass
CN120553999A